School For Talented Students In Asian Countries, A Comparative Study - Ziaeifard, Mahvash; Sharma, Premlata (THE PRIMARY TEACHER, 2008)
This study has been performed regarding the academic standards and rules of school for talented students in Asian Countries. By reviewing the educational system for the gifted, it was evident that Asian countries such as Iran and India are trying their best for achieving higher standard for gifted by educating them in the available education system up to school level. There are no specific educational programmes and some private sectors are active in helping the gifted children in both the countries. The gifted students remained undiagnosed because of only one method used for assessing their giftedness. Since, there are many such students in schools, a more effective system is needed for proper diagnosis and selection of the gifted children.